CITATION INDEX AND OBJECTIVITY OF EXPERTS. ABOUT THE POSSIBLE PHILOSOPHICAL DELIBERATIONS ON THE HOT TOPIC - Lada V. Shipovalova (Высшее образование в России)
The article deals with the actual problem associated with using citation index as an instrument for evaluation of research effectiveness. The author calls in question the propriety of applying SCI: firstly, in ability of the CI to be used in order to improve the effectiveness of science, secondly, in objectivity of CI, thirdly, in the equal opportunity to apply CI to various fields of science. The author argues that SCI use as the means of assessing the effectiveness of science is possible only if the scientific community itself recognizes the CI as a significant element of research, the element of “selfPconsciousness of science”. The article also covers the alternative and no less important than the CI objective grounds for recognizing the value of research, including scientific expertise and discussion. The conclusion is that the insistence on the account of these alternatives promotes recognition of the autonomy of scientific activity, accounting for the value of novelty and originality of scientific ideas and, ultimately, the development of science.